LIBERALIZING SELF-DECEPTION: REPLACING PARADIGMATIC-STATE ACCOUNTS OF SELF-DECEPTION WITH A DYNAMIC VIEW OF THE SELF-DECEPTIVE PROCESS - Pedrini, Patrizia (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2018)
In this paper, I argue that paradigmatic-state accounts of self-deception suffer from a problem of restrictedness that does not do justice to the complexities of the phenomenon. In particular, I argue that the very search for a paradigmatic state of self-deception greatly overlooks the dynamic dimension of the self-deceptive process, which allows the inclusion of more mental states than paradigmatic-state accounts consider. I will discuss the inadequacy of any such accounts, and I will argue that we should replace them with a dynamic view of self-deception that is more liberal regarding the mental states in which self-deceivers may find themselves.